Evaluation of the Expression of Matrix Metalloproteinase-1 of Laryngeal Squamous Cell Carcinoma by Ultrasound Molecular Imaging - Yi Zhou; Yi Zhou; Zhuqing Song; Qiao Hu; Xiaojuan Ji; Hongyu Zheng; Xiaoyan Wang; Zhenzhou Li (Frontiers Media S.A., 2019)
Purpose: The aims of this study were to evaluate the expression of matrix metalloproteinase-1 (MMP-1) on laryngeal squamous cell carcinoma (LSCC) and improve the early diagnosis rate via ultrasound molecular imaging (USMI).Methods: The microsized MMP-1-targeted microbubbles (MBMMP-1) and the control MBs (MBIgG) based on perfluorocarbon-filled lipid-shelled MBs were constructed and characterized. The in vitro binding experiment was performed with human epidermoid laryngeal cancer cells (HEp-2) and tested the binding efficiency of MBMMP-1 and MBIgG. In the in vivo study, the LSCC model was established in 10 mice. The MBMMP-1 and MBIgG were randomly injected into tumor-bearing mice via the tail vein at Day 7, Day 12, and Day 17 to dynamically evaluate the differential targeted enhancement (dTE) signals via USMI. Subsequent immunofluorescence analysis was used for confirmation of MMP-1 expression.Result: The effective adhesion rate of MBMMP-1 and MBIgG to HEp-2 was 298.42 ± 16.57 versus 12.38 ± 3.26 bubbles/per field in vitro experiment, which shows a significant difference (P < 0.01). The in vivo ultrasound molecular imaging (USMI) results demonstrated that dTE signal intensity from MBMMP-1 was significantly higher than that from the MBIgG at Day 7, Day 12, and Day 17 (Day 7, 41.21 ± 15.00 versus 2.25 ± 0.6 a.u., P < 0.05; Day 12, 124.64 ± 5.19 versus 11.13 ± 1.13 a.u., P < 0. 05; Day 17, 332.01 ± 64.88 versus 42.99 ± 11.9 a.u., P < 0.01). Moreover, immunofluorescence analysis further confirmed the expression of MMP-1 in LSCC with a gradual increase with the tumor growth.Conclusion: MBMMP-1 could be a potential probe that can be used in the early diagnosis of LSCC by USMI.